Novel strategies in antithrombotic therapy: targeting thrombosis while preserving hemostasis - Sim, Martha M. S.; Shiferawe, Semekidus; Wood, Jeremy P. (Frontiers in Cardiovascular Medicine, 2023)
Antithrombotic therapy is a delicate balance between the benefits of preventing a thrombotic event and the risks of inducing a major bleed. Traditional approaches have included antiplatelet and anticoagulant medications, require careful dosing and monitoring, and all carry some risk of bleeding. In recent years, several new targets have been identified, both in the platelet and coagulation systems, which may mitigate this bleeding risk. In this review, we briefly describe the current state of antithrombotic therapy, and then present a detailed discussion of the new generation of drugs that are being developed to target more safely existing or newly identified pathways, alongside the strategies to reverse direct oral anticoagulants, showcasing the breadth of approaches. Combined, these exciting advances in antithrombotic therapy bring us closer than we have ever been to the "holy grail" of the field, a treatment that separates the hemostatic and thrombotic systems, preventing clots without any concurrent bleeding risk.